N400 Response Indexes Word Learning from Linguistic Context in Children. Issue 1 (2nd January 2018) - Abel, Alyson D.; Schneider, Julie; Maguire, Mandy J
ABSTRACT: Word learning from linguistic context is essential for vocabulary growth from grade school onward; however, little is known about the mechanisms underlying successful word learning in children. Current methods for studying word learning development require children to identify the meaning of the word after each exposure, a method that interacts with the act of learning. In this study, school-aged children (11–14 years) performed a word learning task as their EEG was recorded. The word learning task required children to identify the meaning of new words presented in sentence triplets that either provided enough context to support word learning or did not provide a supportive context. Children displayed a significant attenuation of the N400 for words for which they identified meanings compared to those for which they were unable to identify meanings. Additionally, the N400 to the final presentation of learned words paralleled that of a known real word. These results indicate that the same mechanisms related to the N400 for extracting word meaning may be associated with word learning in children.